2013
DOI: 10.1210/jc.2012-4122
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Adhesion Molecules, Chemokines, Cytokines, and Tissue Remodeling Factors in Euthyroid Women Without Thyroid Antibodies Who Are at Risk for Autoimmune Thyroid Disease: A Hypothesis on the Early Phases of the Endocrine Autoimmune Reaction

Abstract: Background:The target glands in spontaneous animal models of endocrine autoimmune disease show, prior to the autoimmune reaction, growth and connective tissue abnormalities, whereas the autoimmune reaction is initiated by an early accumulation of macrophages and dendritic cells in the target glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…But at this stage in subjects at risk to develop AITD (like those with a family history of AITD), evidence of immune activation can already be found from a characteristic pattern of serum proteins related to growth/connective tissue abnormalities and migration/accumulation abnormalities of macrophages and dendritic cells (95). In stage II, thyroid antibodies become detectable in serum.…”
Section: Drugsmentioning
confidence: 99%
“…But at this stage in subjects at risk to develop AITD (like those with a family history of AITD), evidence of immune activation can already be found from a characteristic pattern of serum proteins related to growth/connective tissue abnormalities and migration/accumulation abnormalities of macrophages and dendritic cells (95). In stage II, thyroid antibodies become detectable in serum.…”
Section: Drugsmentioning
confidence: 99%
“…A role for other growth factors in the pathogenesis of mood disorders has also been suggested, including a role for PDGF, which has been shown to be altered in the serum of psychiatric patients [34]. We have reported on abnormal serum levels of BDNF and PDGF in patients prone to mood disorders and thyroid autoimmunity [35,36]. …”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of the serum chemokine levels in the ALA, AC, and E. dispar groups revealed several interesting aspects. First, the three groups had equivalently high levels of CCL2, but high serum levels of CCL2 had also been shown in other healthy control groups [ 45 ],[ 46 ]. Second, sex analyses revealed that the male AC subjects had significantly higher CCL2 levels than female AC.…”
Section: Discussionmentioning
confidence: 76%